Dynamic mechanical integrity of cylindrical lithium-ion battery cell upon crushing. (July 2015) - Xu, Jun; Liu, Binghe; Wang, Lubing; Shang, Shi
Graphical abstract: Highlights: A mechanically induced lithium-ion battery integrity criteria is suggested. Dynamic mechanical behavior of lithium-ion battery is investigated using a reasonable dynamic finite element model. Lithium-ion battery mechanical integrity problem under dynamic mechanical loading is comprehensively revealed. Quick engineering guidance for evaluation of battery mechanical integrity under dynamic loadings is provided. Abstract: Lithium-ion batteries are currently widely used in various industries, including automotive industry. Thus, the study of battery mechanical integrity subject to dynamic loading is critical for vehicle safety, which still remains rare. In this paper, first of all, by taking the advantage of previous efforts on quasi-static mechanical experiments on lithium-ion batteries, a new battery mechanical integrity criteria is suggested based on the mechanical strength theory. Further, by considering the strain rate and inertia effect of the battery structural and material, the dynamic mechanical behavior of lithium-ion battery is investigated. Different mechanical failure behaviors are obtained through the combination of numerical simulation and the suggested battery mechanical integrity criteria. Finally, parametric studies are carried out to further comprehensively reveal the battery dynamic mechanical integrity behavior. Results may shed lights on the lithium-ion battery dynamic mechanical behavior and safety research.